Civil Society and Mass Movement: A Historical Perspective and Linkage - Arjun Bhandari (Faculty of Islamic Economics and Business, State Islamic University of Kiai Haji Achmad Siddiq Jember, Indonesia, 2025)
This study investigates the historical development of civil society and its connection to mass movements, with a particular focus on Nepal. Civil society, often regarded as an intermediary between the state and citizens, has played a critical role in advocating for democracy and social justice. The aim of the study is to analyze how civil society organizations (CSOs) have influenced socio-political transformations, particularly during Nepal’s People’s Movements of 1990 and 2006, which were pivotal in restoring democracy and reshaping governance structures. The research employs qualitative and historical methods, relying on secondary data from books, journal articles, and archival records. The study finds that CSOs significantly contributed to mass mobilization by facilitating collective action, amplifying marginalized voices, and advocating for democratic reforms.